Occupational secondhand smoke exposure - A proteomic analysis - Neves, Sofia (2022)
Background: WHO have stated that near 900 000 deaths per year result from exposure to Second- Hand Smoke (SHS). SHS exposure has been linked to cancer, respiratory and cardiovascular diseases and diabetes. However, the associated underlying molecular mechanisms remain to be elucidated. The objective of this proteomics study is to uncover putative key molecules involved in these mechanisms that can be used to predict and monitor diseases risks associated with occupational SHS exposure. Methods: In total, 25 Lisbon restaurants agreed to participate. Nasal epithelium and urine samples were collected from their employees (n=52) for proteomics analysis and cotinine evaluation of SHS exposure, respectively. The subjects were classified as never smoker (N), former smoker (F) and smoker (S); exposed (NE=11; FE=10; SE=4) or non-exposed (N=11; F=8; S=8) to SHS. All subjects were healthy and showed no significant differences in parameters like age, time in the workplace, tobacco smoking habits and spirometry evaluation of pulmonary function. Urine cotinine levels showed significantly elevated in the exposed subjects compared to non-exposed, confirming SHS exposure. Nasal epithelium samples were analyzed by shotgun proteomics using an ESI-LTQOrbitrap mass spectrometer. The “MS raw data” was submitted to “PatternLab for Proteomics” software, with “Comet” search machine algorithm, from where the identified proteins were submitted to a “ClueGO” functional annotation & enrichment analyses in “Cytoscape” software, with the propose to shed some light about the molecular biology involved in the cellular response to the SHS exposition. Results: In NE subjects the SHS is associated with the biologic terms of “Lactate dehydrogenase complex” and “Pentose-Phosphatase Shunt”, also with “Glutathione peroxidase activity” and “Tcell apoptotic process”. At the other end the FE individuals present a specific proteome enriched in biologic information with terms as the “L-Lactate dehydrogenase complex” and the “Peroxisome” as was expected by the results above for the NE cohort; but there were also other different terms as: “Peripheral T cell lymphoma”, “Central carbon metabolism in cancer”, “Myelodysplastic syndrome”, “Monocyte & Granulocyte & Macrophage & Leukocyte Chemotaxis”, Nucleossome, variant H3.1-H2A2-H2B.1&Others” and finally “DNA replication-dependent chromatin assembly”. Conclusions: Proteome of nasal epithelium seems to be modulated by SHS exposure and this is a different and perhaps cumulative process between NE and FE individuals.